Interest Development Theory in Computing Education: A Framework and Toolkit for Researchers and Designers - Michaelis, Joseph E; Weintrop, David (ACM Transactions on Computing Education, 2022)
Computing is rapidly becoming a critical literacy for succeeding in an increasingly technological world. While the proliferation of programs dedicated to broadening participation in computing increases access, computing education research can benefit from more directly drawing on current interest development theory to improve interventions that increase the desire to participate and persist in computing. In this article, we present an overview of current interest development theory and provide guidance to computing education researchers on ways to ground their conceptualization and measurement of interest in contemporary theory and inform ways of interweaving interest theory throughout intervention or curriculum design. The central contribution of this work is presenting the Integrated Interest Development for Computing Education Framework. This framework is organized around three central dimensions of interest: value, knowledge, and belonging. For each of these dimensions, the framework presents key factors that link the dimension to strategies that can be employed in computing education contexts to help develop interest. The article also describes methods of measuring interest in computing that are consistent with interest development theory, and provides examples and resources for validated measures of interest. We conclude with a discussion of the implications and potential for improving the conceptualization and measurement of interest development in computing education and future work needed to advance an understanding of how interest in computing develops that can lead to improving the design of computing educational programs to support interest development.